Post-discharge follow-up of pediatric COVID-19 patients: insights into serological dynamics - Mahmoudi, Shima; Pourakbari, Babak; Shahbabaie, Mohammad Ali; Sotoudeh, Maryam; Jafari, Erfaneh; Hosseinpour Sadeghi, Reihaneh; Mamishi, Setareh (Frontiers in Microbiology, 2024)
Introduction Limited data are available regarding SARS-CoV-2 serological response dynamics in pediatric patients with COVID-19, contributing to gaps in our understanding of the immune response in this population. This study aimed to investigate SARS-CoV-2 IgG seropositivity in patients diagnosed with COVID-19 during hospitalization and 2–4 weeks after discharge. Methods A cohort of patients, consisting of 31 individuals with confirmed acute COVID-19 infection and 27 diagnosed with Multisystem Inflammatory Syndrome in Children (MIS-C), was enrolled in the study. Follow-up clinic appointments were scheduled for 2–4 weeks post-discharge. During admission and follow-up, blood samples were collected from each patient for laboratory analysis. Anti-nucleoprotein SARS-CoV-2 IgG levels were determined using the Enzyme-Linked Immunosorbent Assay (ELISA) method. Results In this study, a cohort of 58 patients was examined. At admission, 52% (n = 14) of MIS-C patients and 10% (n = 3) of acute COVID-19 patients had positive SARS-CoV-2 IgG test. Only 48 cases were referred to the hospital, and follow-up data was available for 20 cases with MIS-C and 28 cases with acute COVID-19. All patients (n = 15) who initially tested positive for SARS-CoV-2 IgG at admission remained positive serology during follow-up (100%). Among the 33 patients who initially tested negative, 12 (37.5%) showed a positive serology result during follow-up, while 21 (62.5%) remained negative. Within this subgroup, 11 cases (44%) were diagnosed with acute COVID-19, and one patient (12.5%) presented with MIS-C. Fourteen cases with acute COVID-19 infection (56%) and seven cases with MIS-C (87.5%) consistently showed negative serology results throughout the study. During follow-up, the median lymphocyte count demonstrated a significant difference, with 0.96 × 109 cells per L (IQR: 0.75–3.0 × 109 cells per L) in the SARS-CoV-2 IgG-negative group and 2.9 × 109 cells per L (IQR = 1.33–7.22 × 109 cells per L) in the SARS-CoV-2 IgG-positive group (p-value = 0.03). Patients who demonstrated seropositivity during the follow-up were associated with a notably severe disease (p-value = 0.028). Conclusion Our study highlights the dynamic nature of SARS-CoV-2 IgG antibody responses in pediatric patients with COVID-19 infection. We observed a notable increase in seropositivity rates during follow-up. Furthermore, patients who were seropositive at follow-up demonstrated a severe disease course and lower lymphocyte counts compared to those with persistently negative serology. Our findings underscore the importance of longitudinal serological monitoring in understanding disease progression and immune response dynamics in pediatric COVID-19 cases.